Exploring alternative approaches to precision medicine through genomics and artificial intelligence – a systematic review - Mumtaz, Hassan; Saqib, Muhammad; Jabeen, Sidra; Muneeb, Muhammad; Mughal, Wajiha; Sohail, Hassan; Safdar, Myra; Mehmood, Qasim; Khan, Muhammad Ahsan; Ismail, Syed Muhammad (Frontiers in Medicine, 2023)
original publications is presented on four main fronts-preventive medicine, medication development, treatment outcomes, and diagnostic medicine-All these studies effectively illustrated the significance of AI in precision medicine. Artificial intelligence (AI) has revolutionized precision medicine by swiftly analyzing vast amounts of data to provide tailored treatments and predictive diagnostics. Through machine learning algorithms and high-resolution imaging, AI assists in precise diagnoses and early disease detection. AI's ability to decode complex biological factors aids in identifying novel therapeutic targets, allowing personalized interventions and optimizing treatment outcomes. Furthermore, AI accelerates drug discovery by navigating chemical structures and predicting drug-target interactions, expediting the development of life-saving medications. With its unrivaled capacity to comprehend and interpret data, AI stands as an invaluable tool in the pursuit of enhanced patient care and improved health outcomes. It's evident that AI can open a new horizon for precision medicine by translating complex data into actionable information. To get better results in this regard and to fully exploit the great potential of AI, further research is required on this pressing subject.